Traumatic knee dislocations: immediate interventions and long-term outcomes - F. Aborukbah, Abdullah; Anbarserri, Faris M.; Almutairi, Maha K.; Elbashir, Hisham A.; Aldawood, Sulaiman M.; Aljabri, Azzam S.; Almunaikh, Mohammed J.; Alhejaili, Mazen L.; Aljohani, Mohammed A.; Bedaiwi, Ahmad H.; Almutairi, Ammar J. (International Journal Of Community Medicine And Public Health, 2024)
Traumatic knee dislocations are severe orthopedic injuries that result from high-energy trauma and involve complete disruption of the tibiofemoral joint. These injuries are rare but represent a significant clinical challenge due to the risk of associated vascular, nerve, and soft tissue damage. Early diagnosis and timely intervention are critical for reducing the risk of permanent disability. The immediate management involves a comprehensive assessment, including history, physical examination, and imaging, followed by the restoration of joint alignment through reduction techniques. Proper management of associated vascular injuries, particularly popliteal artery damage, and nerve injuries, such as peroneal nerve damage, is crucial to prevent long-term complications. Following reduction, knee stabilization and immobilization are necessary to promote healing. Long-term outcomes can be challenging, with complications such as joint instability, post-traumatic arthritis, chronic pain, and the potential for recurrent dislocations. Rehabilitation, which includes range of motion exercises, strength training, and proprioceptive training, plays a vital role in restoring function. In some cases, surgical intervention, including ligament reconstruction or total knee arthroplasty, may be required. This review examines the immediate interventions for traumatic knee dislocations, the associated complications, and long-term outcomes, highlighting the importance of a multidisciplinary approach for optimal recovery and functional restoration.